2013
DOI: 10.1155/2013/312741
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, Antityrosinase, Anticholinesterase, and Nitric Oxide Inhibition Activities of Three Malaysian Macaranga Species

Abstract: The methanol extracts of three Macaranga species (M. denticulata, M. pruinosa, and M. gigantea) were screened to evaluate their total phenolic contents and activities as cholinesterase inhibitors, nitric oxide (NO) production inhibitors, tyrosinase inhibitors, and antioxidants. The bark of M. denticulata showed the highest total phenolic content (2682 mg gallic acid equivalent (GAE)/100 g) and free radical scavenging activity (IC50 = 0.063 mg/mL). All of the samples inhibited linoleic acid peroxidation by grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 28 publications
2
17
1
Order By: Relevance
“…A. cilicia has the lowest inhibitory activities on tyrosinase despite the high content of total phenolics, and strong antioxidant properties compared to other tested extracts. These findings were in contrast with the literature 44,45 where was found a correlation between phenolics content and antityrosinase activity. The lack of correlation can result from the difference in mechanism involved.…”
Section: Enzyme Inhibitory Activitiescontrasting
confidence: 99%
“…A. cilicia has the lowest inhibitory activities on tyrosinase despite the high content of total phenolics, and strong antioxidant properties compared to other tested extracts. These findings were in contrast with the literature 44,45 where was found a correlation between phenolics content and antityrosinase activity. The lack of correlation can result from the difference in mechanism involved.…”
Section: Enzyme Inhibitory Activitiescontrasting
confidence: 99%
“…Similarly, there is also a linear correlation between TPC and tyrosinase inhibitory activity with R 2 value of 0.602. The linkage between AChE and tyrosinase inhibitory activity with neuroprotection as well as an antioxidant test system has been established . From our results EtOAc and n ‐BuOH fractions were notably active against all the tested activities.…”
Section: Resultsmentioning
confidence: 71%
“…The more polar fractions seemed to exhibit a higher activity as compared to the less polar fractions. This may suggest the polarity of the active compounds . The TPC values of methanol extract as well as that in EtOAc, n ‐BuOH and aqueous fractions were relatively high compared to those of the corresponding hexane and DCM fractions.…”
Section: Resultsmentioning
confidence: 96%
“…The result of this study differs from Anjum et al (2013) alleged due to according Salim et al (2016) differences in the place of growth of a species affect the precursors of biosynthesis of secondary metabolites that might be effective to their bioactivity. Mazlan et al (2013) and Tajuddin and Zain (2010) reported that M, gigantea and S. ovalis has weak inhibitory activity against free radical DPPH. However, our finding results demonstrated that G.riedeliana and L. splendens are categorized as very strong antioxidant.…”
Section: Antioxidant Activitymentioning
confidence: 99%